Zika Virus Infection during Pregnancy in Mice Causes Placental Damage and Fetal Demise - Miner, Jonathan J.; Cao, Bin; Govero, Jennifer; Smith, Amber M.; Fernandez, Estefania; Cabrera, Omar H.; Garber, Charise; Noll, Michelle; Klein, Robyn S.; Noguchi, Kevin K.; Mysorekar, Indira U.; Diamond, Michael S. (Cell, 2016)
Zika virus (ZIKV) infection in pregnant women causes intrauterine growth restriction, spontaneous abortion, and microcephaly. Here, we describe two mouse models of placental and fetal disease associated with in utero transmission of ZIKV. Female mice lacking type I interferon signaling (Ifnar1−/−) crossed to wild-type (WT) males produced heterozygous fetuses resembling the immune status of human fetuses. Maternal inoculation at embryonic day 6.5 (E6.5) or E7.5 resulted in fetal demise that was associated with ZIKV infection of the placenta and fetal brain. We identified ZIKV within trophoblasts of the maternal and fetal placenta, consistent with a trans-placental infection route. Antibody blockade of Ifnar1 signaling in WT pregnant mice enhanced ZIKV trans-placental infection although it did not result in fetal death. These models will facilitate the study of ZIKV pathogenesis, in utero transmission, and testing of therapies and vaccines to prevent congenital malformations. [Display omitted] •Establishment of an in utero transmission model of ZIKV infection•ZIKV infects placental cells and results in intrauterine growth restriction•ZIKV infection and injury of the fetal brain is observed•ZIKV infection of fetuses can occur by a trans-placental route Zika virus infection of mice early in pregnancy results in infection of the placenta and fetal brain, causing a fetal syndrome that resembles the intrauterine growth restriction and spontaneous abortion observed in ZIKV-infected pregnant women.